Range of Motion Adaptations During a Simulated Game Exposure in Softball Pitchers - Talmage, Jessica L. Downs; W. Fava, Anthony; Friesen, Kenzie B.; M. Bordelon, Nicole; Oliver, Gretchen D. (International Journal of Sports Medicine, 2023)
Hip and shoulder range of motion (ROM) alterations are correlated with increased risk of injury in softball athletes. The purpose of this study was to investigate bilateral shoulder and hip ROM adaptation during a simulated softball double-header exposure. It was hypothesized that shoulder and hip ROM would decrease after simulated game exposure and would not return to baseline following a 30-minute break. Thirty (14.8±1.9 yrs, 162.5±18.3 cm, 71.79±16.03 kg) adolescent softball pitchers participated. Testing included: bilateral hip and shoulder ROM (preSG), simulated game exposure (100 pitches), bilateral hip and shoulder ROM (postSG), 30-minute break, bilateral hip and shoulder ROM (preDH), pitching first inning of a simulated double header (12 pitches), and bilateral hip and shoulder ROM (postDH). Two separate repeated measures multivariate analyses of variance tests determined differences in ROM between time points. Dominant shoulder internal rotation ROM and non-dominant shoulder internal and external rotation ROM significantly decreased from preDG. Stride hip external rotation ROM and drive hip internal and external rotation ROM significantly decreased from preSG to preDH. Key results revealed the break given between games may not be sufficient recovery time for hip ROM. Thus, assessing ROM as workload progresses can be a useful strategy for monitoring a softball pitcher’s injury risk.
Keywords: hip; musculoskeletal; recovery; shoulder; workload